2022
DOI: 10.3389/fmicb.2022.828636
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Subcellular Localization of the Hepatitis E Virus Replicase: Identification of Candidate Viral Factories

Abstract: Hepatitis E virus (HEV) is the major cause of acute hepatitis worldwide. HEV is a positive-sense RNA virus expressing three open reading frames (ORFs). ORF1 encodes the ORF1 non–structural polyprotein, the viral replicase which transcribes the full-length genome and a subgenomic RNA that encodes the structural ORF2 and ORF3 proteins. The present study is focused on the replication step with the aim to determine whether the ORF1 polyprotein is processed during the HEV lifecycle and to identify where the replica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 49 publications
(86 reference statements)
5
26
0
Order By: Relevance
“…Since ORF3 protein is a key player in the biogenesis of eHEV [33] and CD81 is present on the quasi-envelope [34], the ORF2/ORF3-enriched ultrastructures that we identified likely correspond to eHEV viral factories. In line with this, we recently demonstrated that the ORF1 replicase and genomic RNA are co-distributed with ORF2, ORF3 and Rab11 proteins in nugget-like structures (Fig S9 and [17]). In addition, P1H1, P2H2, P3H2 and 1E6 anti-ORF2 immunolabeling on cryosections of PLC3/HEV cells highlighted in the ORF2-enriched membranous compartments numerous viral-like particles of ~25 nm in diameter (Fig.…”
Section: We Carried Out Double Immunogold Labeling Experiments By Com...supporting
confidence: 76%
See 2 more Smart Citations
“…Since ORF3 protein is a key player in the biogenesis of eHEV [33] and CD81 is present on the quasi-envelope [34], the ORF2/ORF3-enriched ultrastructures that we identified likely correspond to eHEV viral factories. In line with this, we recently demonstrated that the ORF1 replicase and genomic RNA are co-distributed with ORF2, ORF3 and Rab11 proteins in nugget-like structures (Fig S9 and [17]). In addition, P1H1, P2H2, P3H2 and 1E6 anti-ORF2 immunolabeling on cryosections of PLC3/HEV cells highlighted in the ORF2-enriched membranous compartments numerous viral-like particles of ~25 nm in diameter (Fig.…”
Section: We Carried Out Double Immunogold Labeling Experiments By Com...supporting
confidence: 76%
“…ORF3 protein is not involved in virion assembly but plays an essential role in exosomal release and acquisition of the quasi-envelope around the neo- synthesized viral particles [35]. In addition, recent reports by Szkolnicka et al and our laboratory who studied the subcellular localization of the ORF1 replicase using epitope-tagged replicons and full-length genomes found replication complexes in cytoplasmic dot-like structures overlapping significantly with ORF2 and ORF3 proteins as well as HEV RNA ([17, 36] and Fig S9). We can therefore speculate that the observed structures represent viral factories in which assembled particles acquire their membrane through an ORF2-ORF3 interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it remains conceivable that host proteases may post-translationally process ORF1, there is rather limited evidence that subunits of ORF1 itself harbors proteolytic activity. Furthermore, if processing were to occur, it is likely that only a small fraction of ORF1 might be cleaved, as suggested previously(Metzger et al, 2022); however, the smaller species of ORF1 in the previously cited study were unable to be characterized by mass spectrometric analysis, leaving the processing of ORF1 still subject to debate. The inability for the putative HEV PCP to act outside of the context of the full length ORF1 protein suggests that it has some orthogonal activity, and that HEV ORF1 likely functions as one large multi-domain protein.…”
Section: Discussionmentioning
confidence: 68%
“…Mutating C483A, C563A, or H249A are predicted to cause regions of the methyltransferase, helicase, and RdRp to reconfigure ( Figure 5A , right) ( Supplementary Movies 3, 4, and 6, respectively ). Further, mutating C563A, D248A, or H249A causes a predicted membrane association domain that is exposed in the WT ORF1 protein to become buried, possibly preventing the association with intracellular membranes and preventing/hindering the formation of a replication compartment(Metzger et al, 2022; Szkolnicka et al, 2019) ( Supplementary Movies 4, 5, and 6, respectively ). Taken together, these results suggest that by interfering with divalent metal ion binding domains within the putative PCP, structural domains vital to viral replication form aberrantly, and prevent HEV ORF1 from efficiently replicating.…”
Section: Resultsmentioning
confidence: 99%